Analisis dan Konfigurasi Jaringan Multipoint antar Kampus Pusat dan Cabang ITB Indonesia dengan Radiolink Power Beam M5 dan Mikrotik Router Board RB 941 - Nidia Yolanda Olivia; Dani Syahputra; Niken Ayu Syahfitri; Sopia Lorensa Siahaan; Romulo Parlindungan Aritonang; Siti Jamilah Br Tarigan; Ramadani Nasution; Igamawati Giawa (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Wireless computer network allows connecting computers without using cables but using radio waves. Today’s computer networks generally still use cables, with the difference in media, namely air and cable, it takes a tool to combine the two networks with different media. In a wireless network where the user of user’s are connected to the internet using air media through an acces point’ divice. This wireless-based network makes it easier for people to access the internet wherever they are. The design of this network installation consists of installing an RJ- 45 connector on a UTP cable, configuring Power Beam Radio, Access Point, Configuration Server Mikrotik Router Board RB 941, Configuring Bandwidth management, with the existence of a wireless network at the ITB Indonesia Central and Branch campuses, Will make it easier for employees and public to access the internet easily and practically.